AUDIT OF OCCUPATIONAL HEALTH AND SAFETY (OHS) IN A THERMAL POWER PLANT IN THE STATE OF AMAZONAS/BRAZIL: AUDITORIA DE SAÚDE E SEGURANÇA NO TRABALHO (SST) EM UMA USINA TERMELÉTRICA NO ESTADO DO AMAZONAS/BRASIL - Nakanome, Érika Tiaki; Libório, Nicole Sales; Coelho, Moisés Andrade (Brazilian Journal of Production Engineering, 2020)
This research aims to carry out an audit of occupational health and safety (OHS) at a thermal power plant located in the state of Amazonas/Brazil. The research is characterized by quantitative with regard to the problem, exploratory as to the objectives and a case study with respect to the technical procedure. This study used a quantitative survey through the form of auditing and a qualitative survey by the application of direct observation of the productive environment and semi-open interviews. Among the main results achieved, we highlight the systematic analysis of the activities developed in the enterprise through an ergonomic intervention action; identification of risk factors in different sectors through the application of occupational safety and health auditing based on regulatory standards and the study indicates that NRs more focused on worker participation tend to have greater implementation difficulties. The relevance of this study is to demonstrate that ergonomic decisions can be made to improve safety, satisfaction, reducing errors and accidents, aiming to improve the health and productivity of the entire enterprise.